Cognition and neuropsychiatry in behavioral variant frontotemporal dementia by disease stage. (16th February 2016) - Ranasinghe, Kamalini G.; Rankin, Katherine P.; Lobach, Iryna V.; Kramer, Joel H.; Sturm, Virginia E.; Bettcher, Brianne M.; Possin, Katherine; Christine You, S.; Lamarre, Amanda K.; Shany-Ur, Tal; Stephens, Melanie L.; Perry, David C.; et al.
Abstract : Objective: To characterize the cognitive and neuropsychiatric symptoms of patients with behavioral variant frontotemporal dementia (bvFTD) over the natural course of the disease. Methods: We examined the initial and subsequent neuropsychological test performance and neuropsychiatric symptoms in a large cohort of patients with bvFTD (n = 204) across progressive stages of disease as measured by the Clinical Dementia Rating (CDR). We also compared cognitive and neuropsychiatric impairments of patients with bvFTD to those of an age-matched cohort with Alzheimer disease (AD) dementia (n = 674). Results: At the earliest stage (CDR = 0.5), patients with bvFTD had profound neuropsychiatric disturbances, insensitivity to errors, slower response times, and poor naming, with intact attention span, memory, and facial affect naming. Tests continuing to show progressive, statistically significant stepwise declines after the CDR = 1 stage included free recall, visuoconstruction, set-shifting, error insensitivity, semantic fluency, design fluency, emotion naming, calculations, confrontation naming, syntax comprehension, and verbal agility. At CDR = 0.5, patients with bvFTD significantly outperformed patients with AD in episodic memory and were faster in set-shifting, while scoring quantitatively worse in lexical fluency, emotion naming, and error sensitivity. The overall rate of disease progression in bvFTD was more rapid than in AD. Conclusion: There are distinct patterns of cognitive deficits differentiating the earlier and later disease stages in bvFTD, with the pattern of cognitive decline revealing in greater detail the natural history of the disease. These cognitive symptoms are readily apparent clinical markers of dysfunction in the principal brain networks known to undergo molecular and anatomical changes in bvFTD, thus are important indicators of the evolving pathology in individual patients.